The nuclear-encoded plastid ribosomal protein L18s are essential for plant development - Chen, Shujing; Zeng, Xinhuang; Li, Yiqi; Qiu, Shijun; Peng, Xiaoqun; Xie, Xinjue; Liu, Yujie; Liao, Chancan; Tang, Xiaoyan; Wu, Jianxin (Frontiers in Plant Science, 2022)
Plastid ribosomal proteins are necessary components for plastid ribosome biogenesis, playing essential roles in plastid development. The ribosomal protein L18 involved in the assemble of 5S rRNA and 23S rRNA, is vital for E. coli viability, but the functions of its homologs in plant plastid remain elusive. Here, we characterized the functions of the plant plastid ribosomal protein L18s (PRPL18s) in Arabidopsis and rice. AtPRPL18 was ubiquitously expressed in most of the plant tissues, but with higher expression levels in seedling shoots, leaves, and flowers. AtPRPL18 was localized in chloroplast. Genetic and cytological analyses revealed that a loss of function of AtPRPL18 resulted in embryo development arrest at globular stage. However, overexpression of AtPRPL18 did not show any visible phenotypical changes in Arabidopsis. The rice OsPRPL18 was localized in chloroplast. In contrast to AtPRPL18, knockout of OsPRPL18 did not affect embryo development, but led to an albino lethal phenotype at the seedling stage. Cytological analyses showed that chloroplast development was impaired in the osprpl18-1 mutant. Moreover, a loss-function of OsPRPL18 led to defects in plastid ribosome biogenesis and a serious reduction in the efficiency of plastid intron splicing. In all, these results suggested that PRPL18s play critical roles in plastid ribosome biogenesis, plastid intron splicing, and chloroplast development, and are essential for plant survival.